Visual perceptual processing and occupational performance in South African adults with traumatic brain injury - a validity study of the test of visual perceptual skill-3 - Bainbridge, Jane (My University, 2015)
Occupational Therapists use the Test of Visual Perceptual Processing -3 Edition (TVPS-3) to assess clients with Traumatic Brain Injury (TBI) but encounter difficulties as the test is neither standardised in South Africa, nor for adult clients. This study aims to determine the validity of the TVPS-3 for assessing visual perceptual impairment in a sample of South African adults who had sustained TBI and to determine the association with occupational performance competency and values assessed with the Occupational Self- Assessment scale (OSA). Results indicate the TVPS-3 in a South African TBI population to be accurate for sensitivity (80%) and negative predictive value (98%) and can be used reliably as a measure of visual perceptual processing in adult patients with TBI. The z scores on the TVPS-3 account for 20% of the variability seen in the occupational performance competency scores but are not associated with the occupational performance value scores. Although the sample size was relatively small, results of this study show that occupational therapists working with adult clients can use the TVPS-3 confidently to assess residual visual perceptual processing ability. Results also show that reliable associations between clients’ performance on this test and their occupational performance capacity in daily activities can be made. This allows occupational therapists to better predict therapeutic and independent living outcomes with far reaching implications for health care provision, access to care and assisted living facilities and appropriate occupational reintegration.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Occupational Therapy. Johannesburg, 2015